Effects of tannic acid on Haemonchus contortus larvae viability and immune responses of sheep white blood cells in vitro. (February 2014) - Zhong, R. Z.; Sun, H. X.; Liu, H. W.; Zhou, D. W.
Summary Direct inhibitory effects of tannic acid on Haemonchus contortus viability were studied in vitro using the larval migration inhibition (LMI) assay. Sheep white blood cells (WBC) were preincubated with 5 and 50 μg/mL tannic acid or not followed by whole H. contortus antigen (WHA). Cells were harvested at 24 h post‐incubation to test host immune responses. Concentrations of 50, 100, 500, 1000, 3000 and 5000 μg/mL tannic acid inhibited larvae migration by 19·8, 42·4, 46·3, 92·0, 93·7 and 100%, respectively, within 96 h post‐incubation (P < 0·001). The relative mRNA levels of interferon (IFN)‐γ, interleukin (IL)‐2, IL‐4 and IL‐10 were increased by WHA stimulation without tannic acid. However, the increased effects on IFN‐γ and IL‐2 were inhibited by tannic acid preincubation (P < 0·001), while the increases in IL‐4 and IL‐10 were greatly enhanced by tannic acid preincubation (P < 0·001). Changes in protein levels of all cytokines essentially paralleled the changes in their corresponding mRNA levels. In conclusion, tannic acid is directly harmful to larvae in a dose‐ and time‐dependent manner and modulates immune responses of sheep WBC stimulated by H. contortus antigen by inhibiting Th1 cytokines and increasing Th2 cytokine expression in vitro.